UPAYA PENYELESAIAN SENGKETA WILAYAH PERBATASAN DARAT INDONESIA – TIMOR LESTE - Imelda Masni Juniaty Sianipar (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2017)
AbstractOn the Annual Press Statement of the Indonesian Minister for Foreign Affairs 2017, Minister for Foreign Affairs, Retno LP Marsudi stated that Indonesia will accelerate the settlement of negotiations on the border issues of Indonesia with several neighboring countries including Timor Leste. Foreign Minister Retno also stressed that the settlement of Indonesia's border with Timor-Leste will be peaceful, without threat of violence, and with full respect for international law. This article seeks to understand the border dispute of the border areas of Indonesia-Timor Leste in international relations perspective. There are three strategies that Indonesia can implement to resolve this dispute. They are military confrontation, the use of formal institutions such as international organizations and the use of informal institutions such as norms, beliefs, ideas and values. The article argues that it is not enough to rely solely on international agreements to resolve the dispute between Noel Besi / Citrana and Bijael Sunan / Oben, Indonesia needs to emphasize the importance of understanding the norms, beliefs, ideas and values of indigenous peoples living in disputed territories. It is expected that the use of formal and informal institutions can accelerate the settlement of dispute Noel Besi / Citrana and Bijael Sunan / Oben.Keywords: land border dispute, Indonesia, Timor Leste AbstrakPada Pernyataan Pers Tahunan Menteri Luar Negeri Tahun 2017, Menteri Luar Negeri (Menlu) Retno LP Marsudi menyatakan bahwa Indonesia akan mempercepat penyelesaian perundingan masalah perbatasan wilayah Indonesia dengan beberapa negara tetangga, salah satunya adalah Timor Leste. Menlu Retno juga menekankan bahwa penyelesaian perbatasan Indonesia dengan Timor Leste akan dilakukan secara damai, tanpa ancaman kekerasan, dan dengan penghormatan sepenuhnya pada hukum internasional. Artikel ini berupaya memahami sengketa perbatasan wilayah perbatasan Indonesia-Timor Leste dalam perspektif hubungan internasional. Ada tiga strategi yang dapat ditempuh oleh Indonesia dalam rangka menyelesaikan sengketa ini yaitu konfrontasi militer, penggunaan institusi formal seperti organisasi internasional serta penggunaan institusi informal yaitu norma, kepercayaan, ide dan nilai. Artikel ini berargumen bahwa untuk menyelesaikan sengketa Noel Besi/Citrana dan Bijael Sunan/Oben tidak cukup menggandalkan traktat / perjanjian internasional saja, Indonesia perlu lebih menekankan pada pentingnya pemahaman akan norma, kepercayaan, ide dan nilai dari masyarakat adat yang tinggal di wilayah sengketa tersebut. Niscaya penggabungan strategi pemanfaatan institusi formal dan informal tersebut dapat mempercepat penyelesaian sengketa Noel Besi/Citrana dan Bijael Sunan/Oben.Kata kunci: sengketa wilayah perbatasan darat, Indonesia, Timor Leste